The application of budgeting process in public secondary schools in Gauteng South Region - Radebe, Lizzie Zanyiwe (My University, 2013)
A budget is an action plan that is utilized by organisations, private or public, in order to attain their objectives. Budgets are used to ensure better financial performance for organizations. They are also used to identify financial problems and take appropriate corrective measures. Public secondary schools also prepare their budgets to plan for their income and expenditure. It is through developing their budgets that public secondary schools are able to achieve their visions and missions. The purpose of the study is to evaluate the extent to which the budgeting process is effectively implemented in public secondary schools in the Gauteng South Region. To achieve this objective a questionnaire was developed to elicit responses from the participants in the research. The questionnaire was a closed-ended one with two sections, A and B. Section A of the questionnaire was developed to gather biographical information about the units of analysis, whereas Section B dealt with key issues pertaining to the budgeting process. The reliability of the questionnaire was tested through Cronbach’s alpha coefficient. The feedback from the questionnaire was analysed by means of Exploratory Factor Analysis where five factors were extracted and their reliability also tested. The factor loading matrix was computed to identify appropriate items for each factor. The items were analysed using frequencies in respect of each factor. Correlations analysis for the factors was conducted to determine the relationship between them. The findings from the study indicate that: budget planning assists school managers in comparing income and expenditure; coordination of budgeting activities is a problem at schools; lack of communication stifles effective implementation of the budget; there is no effective training and development for those involved in the budgeting process; the financial targets are not set and communicated to key stakeholders; there is lack of budget control and monitoring measures of variances of the planned and actual budget is non-existent; educators are not offered the opportunity to participate in the budgeting process let alone have the authority to make decisions on budgetary issues for those who are involved. The value of this research lies in setting appropriate guidelines for effective implementation of the budgeting process. Effective implementation of the budgeting process will facilitate efficient delivery of quality education to learners. The importance of the study is that it offers various types of budgets that public secondary schools can use to remain financially viable and sustainable.
Keywords: Budget, employee participation, employee empowerment; Accounting -- Budget; Budget process -- South Africa; Dissertations, Academic -- South Africa